Are shariah-compliant structured products able to withstand global financial shocks? A new perspective on the performance of shariah-compliant structured investment-linked plans in Malaysia - Rahman, Maya Puspa; Kassim, Salina (Statistical, Economic and Social Research Training Centre for Islamic Country, 2017)
Islamic structured product is a shariah-compliant asset class that is considered as a recent innovation in the financial market. In view of the increasing presence of Islamic finance in the global financial scenario, research on Islamic structured product has captured substantial interests among the investment community searching for new alternatives, particularly during uncertain market conditions. This study aims to serve as one of the pioneering empirical references for investors to evaluate Islamic structured investments, and for the regulators to strengthen the regulatory framework for such products in order to continuously protect investors’ interests and provide a conducive environment for further growth of the industry